IFPRI Egypt Strategy Support Program Workshop Goal, Objectives, and Procedures - Ecker, Olivier (2016)
Workshop Goal, Objectives, and Procedures for IFPRI's Egypt Strategy Support Program Research Priority Setting Workshop, by Olivier Ecker, IFPRI